9-phenyl acridine photosensitizes A375 cells to UVA radiation. Issue 9 (September 2020) - Hansda, Surajit; Ghosh, Gargi; Ghosh, Rita
Abstract: Acridines are an important class of bioactive molecules having varied uses. Its derivative, 9-phenylacridine (ACPH) had been found to exhibit antitumor activity both in cell lines and in vivo model. Its DNA binding ability and absorbance in the ultraviolet range encouraged us to investigate its role as a photosensitizer with UVA radiation. We investigated the effects of ACPH prior to UVA exposure on in vitro DNA through photo-cleavage assay. Effect of such treatment was also studied in cultured A375 melanoma cells. Endpoints studied included morphological changes, evaluation of cellular viability, scratch assay, intracellular reactive oxygen species (ROS) production, DNA damage, lipid peroxidation, glutathione (GSH) level, autophagy, cell cycle progression, depletion of mitochondrial membrane potential (ΔΨmt), induction of apoptosis and Hoechst dye efflux assay. Our findings indicated that ACPH could sensitize damage to DNA induced by UVA both in vitro and in cells. It could also potentiate cell killing by UVA. It arrested cells in G2 /M phase and induced apoptotic death through mitochondria mediated pathway. This sensitization was through enhancement of intracellular ROS. Our findings also indicated that the stem cells side population was reduced on such treatment. The findings are important as it indicates ACPH as a promising photosensitizer and indicates its possible role in photodynamic therapy. Abstract : Cell biology; Biochemistry; Molecular Biology; Cancer Research; Toxicology; 9-phenyl acridine; A375 cells; photosensitization; ROS; DNA damage; apoptosis